Legal Responsibilities Of Bandung's OKKO Bakery In Ensuring Product Safety Under Consumer Protection Law Number 8 of 1999 - Andi Khuswatun Khasana; Amad Sudiro (Magister Hukum Universitas Semarang, 2025)
This research aims to investigate the legal liability of OKKO Bandung bakery regarding product safety compliance under Indonesia's Consumer Protection Law No. 8 of 1999, particularly following a BPOM investigation that identified unauthorized food additives in their bread products. The urgency of this study stems from increasing violations of consumer rights in the food industry, where producers fail to meet safety standards, potentially endangering public health. This research employs a comprehensive qualitative methodology, combining normative legal analysis with empirical fieldwork through structured interviews and systematic observations. The study reveals that producers bear significant legal obligations to ensure product safety, provide transparent product information, and offer appropriate compensation for damages. This research contributes new insights through its unique combined normative-empirical approach, analyzing actual court precedents demonstrating implementation gaps between legal theory and enforcement reality. The study proposes specific regulatory reforms, including mandatory third-party ingredient verification, enhanced supply chain transparency, and strengthened inter-agency coordination to effectively safeguard public health and consumer interests.